2016
DOI: 10.1007/jhep03(2016)208
|View full text |Cite
|
Sign up to set email alerts
|

3D holography: from discretum to continuum

Abstract: Abstract:We study the one-loop partition function of 3D gravity without cosmological constant on the solid torus with arbitrary metric fluctuations on the boundary. To this end we employ the discrete approach of (quantum) Regge calculus. In contrast with similar calculations performed directly in the continuum, we work with a boundary at finite distance from the torus axis. We show that after taking the continuum limit on the boundary -but still keeping finite distance from the torus axis -the one-loop correct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(92 citation statements)
references
References 133 publications
10
82
0
Order By: Relevance
“…These can be taken as boundary field variables, and one can thus easily integrate out all variables except these boundary field variables. [14] also computed the one-loop partition function for a finite boundary, which led to the same result as for asymptotically flat boundaries [18], see [19] for a corresponding result for asymptotic AdS boundaries.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…These can be taken as boundary field variables, and one can thus easily integrate out all variables except these boundary field variables. [14] also computed the one-loop partition function for a finite boundary, which led to the same result as for asymptotically flat boundaries [18], see [19] for a corresponding result for asymptotic AdS boundaries.…”
mentioning
confidence: 75%
“…Using metric boundary data [14] showed that a Liouville like dual field theory can also be identified more directly for finite boundaries. This work considered a specific background space time, so-called twisted thermal flat space [15], and employed (linearized) Regge calculus [16], a discretization of gravity, in which the variables are given by edge lengths in a piecewise flat geometry.…”
mentioning
confidence: 99%
“…The BMS character is in fact well-defined on the upper complex plane, and can be identified as the Dedekind η-function up to a factor. This formula was also re-derived as an asymptotic limit of Regge calculus for discretized 3D gravity in [68]. It was further recovered as leading order of a WKB approximation of the Ponzano-Regge model with LS spin network boundary states in [3].…”
Section: Poles and Exact Residue Formula For The Free Ponzano-reggmentioning
confidence: 88%
“…On the other hand, the less compact formula (95) gives the explicit expansion of the partition function in the momentum basis and shows the poles in γ. As we will discuss in the next section, this latter expression allows for a clearer continuum limit, where we will recover the BMS character formula for the 3D quantum gravity path integral, as derived in [22,23,68].…”
Section: Poles and Exact Residue Formula For The Free Ponzano-reggmentioning
confidence: 90%
See 1 more Smart Citation